Endogeneity of Monetary Policy Reaction Fun~tion: An Experience from Pakistan's Economy (The Pakistan Development Review, 1991)
Monetary policy, in general, refers to those steps taken by the Central Bank to achieve such broader objectives of the economy as growth, employment, external balance and price stability through changes in the money supply, interest rates and credit policies. The money supply thus created by the Central Bank should be in response to the changes in key macroeconomic target variables such as GNP, balance of payments, inflation, internal debt and unemployment. Indeed, a properly estimated monetary policy reaction function can provide useful information regarding such matters as to whether the Central Bank, in fact, has been systematically accommodating to the changes in the target variables. The reaction function can also provide insight into the question as to what should be the relevant indicators of the monetary policy. In addition, as argued by Havrilesky (1967), it may also play a crucial role in the formulation of long-term monetary policy strategy. The other important consideration in the development of a monetary policy reaction function pertains to the endogeneity of the monetary policy. As pointed out by Goldfeld and Blinder (1972), if a policy variable responds to the lagged (or expected) target values, then considering such a policy variable as exogenous would not only introduce the problem of misspecification but will also produce serious biases in the parameters estimated from those models. In particular, if the monetary policy variable happens to be strongly influenced by target variables, then the standard result of the relative effectiveness of the monetary policy vis-a-vis fiscal policy can be questionable on the grounds of reverse causation problem.